Morphological changes in maize subjected to different nitrogen rates in a low-altitude subtropical environment - Ferrari, Felipe Santi; Rosa, Guilherme Bergeijer da; Santos, Emilso Damm dos; Marques, Anderson César Ramos; Monteiro, Eduardo Castiglioni; Follmann, Diego Nicolau (OBSERVATÓRIO DE LA ECONOMÍA LATINOAMERICANA, 2025)
This study aimed to evaluate the effects of nitrogen rates on the morphology of maize grown in a low-altitude subtropical environment. The experiment was conducted during the 2023/2024 growing season in an experimental area located in Santa Maria, Rio Grande do Sul, Brazil. The DKB 230 PRO 3 hybrid was sown in a randomized block design with three replications and six treatments. The treatments consisted of different nitrogen rates applied as topdressing: T1 – no nitrogen application; T2 - 50 kg de N ha-1; T3 - 100 kg de N ha-1; T4 - 150 kg de N ha-1; T5 - 200 kg de N ha-1 e T6 - 250 kg de N ha-1. Nitrogen was applied in two split doses: 50% at the V4 growth stage and 50% at the V8 stage. The evaluated variables included plant height, stem diameter, leaf area, ear length, and the total number of grains. Data were subjected to regression analysis and Pearson correlation. The results indicated that the 250 kg N ha-1 rate resulted in the highest values for plant height, leaf area, ear length, and the total number of grains. Furthermore, significant linear correlations were observed between plant height and stem diameter, plant height and leaf area, and stem diameter and leaf area. Based on these findings, it can be concluded that the application of 250 kg N ha-1 maximizes maize growth and productivity, making it the most effective nitrogen rate for optimizing crop performance.